1996
DOI: 10.1021/la951503z
|View full text |Cite
|
Sign up to set email alerts
|

Infrared and Resonance Raman Spectroscopic Study on the Photopolymerization Process of the Langmuir−Blodgett Films of a Diacetylene Monocarboxylic Acid, 10,12-Pentacosadiynoic Acid

Abstract: Absorption, infrared reflection absorption (IRA), and resonance Raman scattering (RRS) spectroscopies were applied to obtain direct information about the conformation change of a polydiacetylene (abbreviated to PDA) produced by UV irradiation of the Langmuir−Blodgett (LB) films of the cadmium salt of a diacetylene derivative, 10,12-pentacosadiynoic acid (DA), with the number of monolayers from 1 to 31. The rate and extent of the polymerization of DA monitored by the relative intensity change of the IRA bands d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 20 publications
6
78
0
2
Order By: Relevance
“…Previously, it has been suggested that the red-phase PDA is in more disordered state than the blue-phase counterpart. [84] However, observations made with AFM images of the blueand red-phase PDAs confirm the alkyl chains in red-phase PDAs exist in a more ordered state. [85] The observations made with AFM images, 13 C NMR data reported by Tanaka et al, [86] and theoretical calculations from Tripathy et al, [78] have led to the suggestion that the shear forces imposed on the PDA film induce sidechain rotation about the conjugated backbone which reduce the effective conjugation length of the polymer.…”
Section: Mechanochromismmentioning
confidence: 97%
“…Previously, it has been suggested that the red-phase PDA is in more disordered state than the blue-phase counterpart. [84] However, observations made with AFM images of the blueand red-phase PDAs confirm the alkyl chains in red-phase PDAs exist in a more ordered state. [85] The observations made with AFM images, 13 C NMR data reported by Tanaka et al, [86] and theoretical calculations from Tripathy et al, [78] have led to the suggestion that the shear forces imposed on the PDA film induce sidechain rotation about the conjugated backbone which reduce the effective conjugation length of the polymer.…”
Section: Mechanochromismmentioning
confidence: 97%
“…1) [1,2,4,5]. The unperturbed PDA vesicles, in which the side chains arrange in an ordered fashion, exhibit a deep blue color [1,2,30,31]. The increase of temperature promotes the dynamics of side chains, which eventually breaks the hydrogen bonds at the surface of PDA vesicles [1,5,27,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…This conformation is affected by the orientation and packing of the hydrocarbon side chains pendant to the backbone that can either alter the length or change the mode of n-conjugation (10). A variety of analytical techniques, such as electron diffraction (11), FT-IR (12), resonance Raman (13), and fluorescence polarization (14), have been employed to identify the molecular orientation of the side chains and backbones.…”
Section: Introductionmentioning
confidence: 99%